Overcoming flowering asynchrony in date palm through pollen management - Ganeshan, A; Sharma, S. K.; Anushma, P. L.; Janakiram, T. (Indian Horticulture, 2019)
Date palms are one of the first plants that were cultivated by man and some of the date palm varieties are thousands of years old! Date palms are dioecious, which means that there are both male date palms and female date palms. After reaching maturity, male date palm yields flowers that produce the pollen. The female date palm yields flowers which will become dates, if they are pollinated. The male flowers are borne single and are waxy white, while the female flowers are borne in clusters of three and are yellowish green in colour. A preliminary study with ICAR-IIHR was carried out to study the feasibility to store pollen at low temperatures for stockpiling pollen of superior branded male date palms. This would facilitate inter-region/country exchange of pollen, establishment of a Pollen Cryorepository for 24Ã—7 supply of viable pollen during female flowering for pollination. Cold packed date palm pollen was brought to IIHR, Bengaluru, from CIAH, Bikaner, and germinated in-vitro within 48 hours of collection. Date palm pollen cryopreserved for 6 hours germinated showing cryofeasibility. The cryopreserved pollen of branded high prized superior males with high germination profiles can be commercially marketed for pollination through a cryorepository. Pollen of advanced breeding lines can be maintained in the cryorepository for shuttle breeding and transboundary exchange can be facilitated through networking between date palm growing regions/countries for effective pollen management.